Sedimentary Rock Magnetic Response to Holocene Environmental Instability in the Pearl River Delta - Wu, Yi; Fu, Shuqing; Xiong, Haixian; Zong, Yongqiang; Ouyang, Tingping; Peng, Shasha; Cai, Jianxin; Han, Yulin; Zhu, Zhaoyu (Frontiers in Earth Science, 2022)
Located on the northern coast of the South China Sea, the densely-populated Pearl River Delta has experienced the combined effects of sea level change, monsoon-driven discharge, and especially human activity, since the late Holocene. However, how these factors have regulated the regional environmental and sedimentary evolution remain unclear. To better understand these processes we conducted a high-resolution rock magnetic investigation of the Holocene sediments of core DS01, drilled in the vicinity of the West River channel in the head area of the Pearl River deltaic plain. The magnetic grain-size proxy of ARM/κlf ratio (the ratio of anhysteretic remanent magnetization to low-field magnetic susceptibility) indicates a long-term fining trend of the magnetite grain size, which may be a response to an increase in the weathering intensity in the Asian monsoon region during the Holocene. An interval with an enhanced concentration of magnetic minerals (mainly magnetite and hematite) occurred during 7.7-4.8 kyr BP (calendar years before 1950), coincident with a period of delta progradation. During the marine transgression in the early Holocene, two similar intervals of magnetic enrichment may reflect regional hydrodynamic shifts associated with cooling events at ~9.5 – 9.3 kyr BP and 8.2 kyr BP. The subsequent 4.2 kyr BP cooling event possibly induced a cold and dry environment in the sediment source area. From ~800 yr BP onwards, there was a major increase in the sedimentary magnetic mineral content, likely in response to intensified agricultural and industrial activities.